MECHANISMS FOR GOVERNMENT REGULATION OF ENERGY RESOURCE USE - Меlnychenko O.A.; Lohozynskyi O.О. (Pressing Problems of Public Administration, 2018)
The classification of mechanisms for government regulation of energy resources use has been upgraded. The list of priority areas of energy consumption improvement has been specified.